Growth during puberty in cystic fibrosis: a retrospective evaluation of a French cohort. Issue 8 (12th June 2012) - Bournez, Marie; Bellis, Gil; Huet, Frédéric
Abstract : Objectives: To assess the longitudinal growth pattern in a large French cohort of patients with cystic fibrosis (CF), to determine to what extent puberty contributed to final height and to explore a potential relationship between growth, nutritional status and respiratory function. Methods: Retrospective data were drawn from the French CF registry from 1999 to 2004. Height, weight and forced expiratory volume in 1 s (FEV1 ) were recorded annually. Growth and velocity curves were compared with reference curves. Results: 729 children with CF were included. In girls, height was similar to the reference population until age 11. Age at onset of puberty was the same as in reference girls. The pubertal spurt was lower than reference values and contributed less to the final adult height. In boys, the mean height was close to the reference mean until age 14 and was thereafter lower. Age at growth acceleration was similar to that in reference boys, but with an impaired peak height velocity (PHV). The final height was lower than in the general population (z score −0.73). No correlations were found between body mass index (BMI) and PHV. In girls, there was a weak but significant positive relationship between PHV and FEV1 (r=0.17, p=0.02) Conclusions: In this cohort, children with CF had a normal age of onset of puberty and pubertal spurt, with a low PHV. Puberty contributed less to final adult height, and neither BMI nor FEV1 had a significant effect on pubertal height gain.